Intracerebral Hemorrhage Induces Cardiac Dysfunction in Mice Without Primary Cardiac Disease - Li, Wei; Li, Linlin; Chopp, Michael; Venkat, Poornima; Zacharek, Alex; Chen, Zhili; Landschoot-Ward, Julie; Yan, Tao; Chen, Jieli (Frontiers in Neurology, 2018)
Background: Intracerebral hemorrhage (ICH) is a life threatening stroke subtype and a worldwide health problem. In this study, we investigate brain-heart interaction after ICH in mice and test whether ICH induces cardiac dysfunction in the absence of primary cardiac disease. We also investigate underlying mechanisms such as oxidative stress and inflammatory responses in mediating cardiac dysfunction post-ICH in mice. Methods: Male, adult (3-4m) C57BL/6J mice were subjected to sham surgery or ICH using an autologous blood injection model (n=16/group). Cardiac function was evaluated at 7 and 28 days after ICH using echocardiography (n=8/group per time point). Western blot and immunostaining analysis were employed to assess oxidative stress and inflammatory responses in the heart. Results: Mice subjected to ICH exhibited significantly decreased cardiac contractile function measured by left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) at 7 and 28 days after ICH compared to sham-control mice (p<0.05). ICH induced cardiac dysfunction was significantly worse at 28 days than at 7 days after ICH (p<0.05). ICH in mice significantly increased cardiomyocyte apoptosis, inflammatory factor expression and inflammatory cell infiltration in heart tissue, and induced cardiac oxidative stress at 7 days post-ICH compared to sham-control mice. Compared to sham-control mice, ICH-mice also exhibited significantly increased (p<0.05) cardiomyocyte hypertrophy and cardiac fibrosis at 28 days after ICH. Conclusions: ICH induces significant and progressive cardiac dysfunction in mice. ICH increases cardiac oxidative stress and inflammatory factor expression in heart tissue which may play key roles in ICH-induced cardiac dysfunction.